STRATEGI BRAND IMAGE DALAM MENINGKATKAN MUTU PENDIDIKAN PADA LEMBAGA PENDIDIKAN SDIT BUNAYYA DI KOTA LHOKSEUMAWE - Novi, Novi Hardiana (Postgraduate Program UIN Sultanah Nahrasiyah Lhokseumawe, 2024)
The strategy of building brand image in improving the quality of education at SDIT Bunayya Lhokseumawe City and describing the strategy of maintaining brand image in improving the quality of education at SDIT Bunayya Lhokseumawe City. This type of research is qualitative research using a prescriptive approach. The data sources in this research are primary data and secondary data. The data collection method in this study is by conducting interviews, observation, and documentation. The steps used in this research consist of data reduction, data presentation, and conclusions. The data analysis method uses content analysis techniques. The results showed that, First, the strategy of building a brand image of SDIT Bunayya Educational Institution in Lhokseumawe City consists of: conducting SWOT analysis, building integration, differentiating, and having quality alumni. Second, the strategy to maintain the brand image of SDIT Bunayya Education Institution Lhokseumawe City consists of: carrying out accreditation, conducting evaluations, improving services and trust, and promoting the institution.